Natural convective flow of a magneto-micropolar fluid along a vertical plate - M. Ferdows; D. Liu (Propulsion and Power Research, 2018)
This paper presents a numerical study of natural convective flow of an electrically conducting viscous micropolar fluid past a vertical plate. Internal heat generation (IHG) versus without IHG in the medium are discussed in the context of corresponding similarity solutions. Results are presented in terms of velocity, angular velocity, temperature, skin friction in tabular forms, local wall-coupled stress, and Nusselt number. Computations have been accomplished by parametrizing the micropolar, micro-rotation, magnetic field, suction parameters, and the Prandtl number. Several critical issues are addressed at the end of the paper with reference to a previous study by El-Hakiem. The study is relevant to high-temperature electromagnetic materials fabrication systems. Keywords: Natural convection, Thermal boundary layer, Micropolar fluid, Similarity transformation, Internal heat generation